Federated States of Micronesia : Climate Change Policy Assessment. (IMF Staff Country Reports; Country Report ;, 2019)
This Climate Change Policy Assessment (CCPA) takes stock of the Federated States of Micronesia (FSM)'s climate response plans, from the perspective of their macroeconomic and fiscal implications. CCPA explores the possible impact of climate change and natural disasters and the cost of FSM's planned response. It suggests macroeconomically relevant reforms that could strengthen the national strategy and identifies policy gaps and resource needs. FSM has made progress toward its Nationally Determined Contribution mitigation pledge by beginning to expand renewable power generation and improve its efficiency. The authorities plan to continue this and encourage the take-up of energy efficient building design and appliances. Accelerating adaptation investments is paramount, which requires addressing critical capacity constraints and increasing grant financing. It is recommended that FSM needs to increase its capacity to address natural disaster risks following the expiry of Compact-related assistance in 2023. It is advised to improve climate data collection and use, including on the costs of high and low intensity disasters and disaster response expenditure.